Perencanaan Dan Perancangan Tempat Wisata Pengolahan Susu Sapi Di Wilayah Boyolali Jawa Tengah - Veronica Amalia Samputri; Putri Suryandari (MAESTRO, 2019)
Planning and Design of Cow Milk Processing Places in Boyolali is a facility that provides tourist attractions as well as educational sites for visitors. This place offers a variety of facilities such as diary cow milk farms, visitors here can see directly the process of milking cow until when sterilizing cow's milk, the process of making cow's milk is processed into foods such as dodol milk, tofu milk, etc. Store a place where food is mostly made from milk. Planning and Designing of Cow Milk Processing Tourism Site is located in the Boyolali region of Central Java, precisely in the village of Cepogo. With the concept of Modern Traditional Architecture visitors can experience first hand the process of milking cows and try to untie climate conditions in Indonesia with their application to land and buildings.